Pengaruh Pendidikan Kesehatan dan Pemberian Daun Seledri pada Pasien dengan Hipertensi di Wilayah RT 10 Kelurahan Murni - Amelia Ade Anggraini; Vevi Suryenti Putri; Zuli Nuranti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Hypertension is a non-communicable disease which is an important health problem throughout the world because its prevalence is quite high and continues to increase and its relationship with cardiovascular disease, stroke, retinopathy, and kidney failure. Based on the assessment conducted through interviews, observations, and distribution of questionnaires obtained data in RT 10 Kelurahan Murni with a total of 47 families and 172 inhabitants of the population of 39 elderly obtained hypertension percentage of 38.7% and 50% of the community if sick only take medication from shop. Counseling activities carried out for 45 minutes with the stages of directing participants to the place to be counseling, opening which was delivered by the moderator, delivering counseling material delivered by the presenter, demonstrating how to make a decoction of celery leaves, evaluating the extension participants, distributing leaflets to participants and documenting activities. The results of counseling 80,56% of participants were able to explain the understanding of hypertension, mention the causes of hypertension, 77,78% mention the signs and symptoms of hypertension, 77,7% explain the prevention of hypertension, 83,33% mention foods that are allowed, 86,11% mention foods that are not allowed, 86,11% can make herbal ingredients using celery leaves.